2021
DOI: 10.1002/agg2.20194
|View full text |Cite
|
Sign up to set email alerts
|

Soil quality assessment of an agroforestry system following long‐term management in the Ozark Highlands

Abstract: The Soil Management Assessment Framework (SMAF) is a quantitative soil quality (SQ) evaluation tool that is widely applied to assess soil response to specific agricultural management practices over time. Considering the reported SQ benefits of agroforestry (AF) systems and the potential usefulness of SMAF, the objective of this study was to evaluate the effects of tree species (pecan [Carya illinoinensis (Wangenh.) K. Koch] and northern red oak [Quercus rubra L.]), soil fertility source (poultry litter [PL] a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…These results agreed with previous reports in the literature and demonstrated that SOM accumulation plays a major role in nutrient cycling and availability in AF systems [2,4]. Our findings may represent a guideline for improving the SOM accumulation, SOC retention, and fertility in temperate AF systems and, therefore, an opportunity to offset anthropogenic CO 2 emissions and improve soil quality [43].…”
Section: Soil Properties In 2016: Linkagessupporting
confidence: 92%
See 1 more Smart Citation
“…These results agreed with previous reports in the literature and demonstrated that SOM accumulation plays a major role in nutrient cycling and availability in AF systems [2,4]. Our findings may represent a guideline for improving the SOM accumulation, SOC retention, and fertility in temperate AF systems and, therefore, an opportunity to offset anthropogenic CO 2 emissions and improve soil quality [43].…”
Section: Soil Properties In 2016: Linkagessupporting
confidence: 92%
“…These results demonstrated that poultry litter applications increased the overall soil fertility compared to the control treatment (inorganic fertilizer), with more pronounced effects in 2008. Organic fertilizers, such as animal manures, have been shown to neutralize soil acidity, increase nutrient levels, and improve biological activity and diversity relative to inorganic fertilizers, thus contributing to improved soil health [41][42][43].…”
Section: Oak Pecanmentioning
confidence: 99%
“…This stronger relationship suggests a greater dependence on receiving adequate precipitation for annual systems. Conversely, perennial systems were able to maintain near-normal (93%-112% of their expected productivity) under low-precipitation conditions, thus suggesting deep rooted perennial systems with greater diversity and likely greater microbial diversity and soil health (Gurmessa et al, 2021;Ylagan et al, 2021) are critical to sustainable food production, especially under current and future stochastic climatic conditions. Similarly, Sanford et al (2021) compared annual row crop systems with perennial systems in a 26-year experiment in the North Central United States and found that more diverse, perennial systems exhibited greater resilience under drought.…”
Section: Resiliency Estimates For Perennial and Annual Systems Under ...mentioning
confidence: 99%
“…Specific details on the 2016 to 2021 tree fertilizer amounts and application areas per tree species are presented on Table 1. Additional site establishment and management details have been reported [15,[17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Fertilizer Applicationsmentioning
confidence: 99%